Additively Manufactured Deformation‐Recoverable and Broadband Sound‐Absorbing Microlattice Inspired by the Concept of Traditional Perforated Panels - Li, Xinwei; Yu, Xiang; Zhai, Wei (Advanced materials (Weinheim), 2021)
Noise pollution is a highly detrimental daily health hazard. Sound absorbers, such as the traditionally used perforated panels, find widespread applications. Nonetheless, modern product designs call for material novelties with enhanced performance and multifunctionality. The advent of additive manufacturing has brought about the possibilities of functional materials design to be based on structures rather than chemistry. With this in mind, herein, the traditional concept of perforated panels is revisited and is incorporated with additive manufacturing for the development of a novel microlattice‐based sound absorber with additional impact resistance multifunctionality. The structurally optimized microlattice presents excellent broadband absorption with an averaged experimental absorption coefficient of 0.77 across a broad frequency range from 1000 to 6300 Hz. Extensive simulation and experiments reveal absorption mechanisms to be based on viscous flow, thermal and structural damping dissipations while broadband capabilities to be on multiple resonance modes working in tandem. High deformation recovery up to 30% strain is also possible from the strut‐based design and viscoelasticity of the base material. Overall, the excellent properties of the microlattice overcome tradeoffs commonly found in conventional absorbers. Additionally, this work aims to present a new paradigm: revisiting old concepts for the developments of novel materials using contemporary methods. Based on traditional perforated panel concepts, a novel broadband sound‐absorbing microlattice with impact‐recovery multifunctionality is presented. The microlattice boasts high averaged absorption coefficients of 0.77 with mechanisms attributing to synergistic impedance matching and a combination of viscous, thermal, and structural damping dissipation. It is also pseudo‐reusable with high strain recovery at 30% with no degradation of sound absorption observed.